(untitled) (Research, Society and Development, 2023)
This study aimed to investigate formative elements that are present in speeches and practices of teachers involved in a process of curricular restructuring, via Study Situation (SE), during the period of effectiveness of the New High School (NEM), and to analyze the contributions of this process in the Teacher Professional Development (DPD). This is a qualitative research, action-research modality, developed in a state public school located in the Northwest of the State of Rio Grande do Sul/RS. This research involved three elementar school teachers, a teacher from a Regional Education Coordination in RS, who answered an interview, and a teacher and four students from a community university. The data were organized by the bias of a Discursive Textual Analysis (DTA), resulting in two categories: a) resistance and b) teacher identity. The results reveal that curricular changes, whether via educational policies or as a result of self-reflective processes of curricular restructuring promoted by the school itself, provide opportunities for educational work that improve the processes of human and professional development of those who are involved. They also demonstrate that resistance, in the investigated context, suggests transformations in the subject and in the constitution of his/her personality, and the teacher’s identity takes place in the interrelationship between personal and professional knowledge and the ability to appropriate that knowledge that quality educational work requires.